Energy budget trends over the Korean peninsula in the past 20 years - Lee, Soo-Min; Park, Yeonwoo; Choi, Jun Ahn (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The term “Energy Budget” represents the incoming solar energy, outgoing amounts of energy, and the energy retained in the Earth’s atmosphere. This article aims to analyze the energy budget trend in the Korean Peninsula over the period from 2001 to 2022, focusing on the Earth’s Energy Imbalance (EEI) and the role of cloud cover and how it influences shortwave (SW) and longwave (LW) radiation. Using the dataset obtained from NASA’s CERES satellite, the article investigates the amount of reflected and emitted energy globally and compares it with the Korean peninsula. The findings indicate that globally, the total wave which is the sum of all longwave, shortwave, and cloud shortwave radiation has increased in trend. The plot also displays a decrease in Cloud fraction (CL fraction) or cloud coverage. Contrary to this, the Korean peninsula displayed a relatively stable level of total radiation and an increase in CL fraction. However, further analysis is needed to understand the factors behind these regional differences, including the potential influence of monsoon circulation patterns.